Efektivitas Penggunaan Bahan Ajar Video Interaktif Hak Asasi Manusia (VIKTIF HAM) untuk Perkuliahan Hak Asasi Manusia - Rarasati, Ida Putri; Trihastuti, Meiwatizal; Baihaqi, Muhammad Iqbal (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2020)
This article was to determine the validity, practicality testing and effectiveness of human rights learning. The method used research and develeopment (RnD) that aims to develop multimedia Viktif HAM teaching materials, to test the effectiveness of teaching materials in achieving learning objectives. The results showed that in the developing Viktif HAM teaching materials, was knowing potential problems and collecting data, making prototypes of teaching materials, conducting expert validation and revision, small and large scale field trials. Based on the results of expert validation, the developed teaching materials are in the very valid category with an average validation score of 89.2% in all aspects of assessment. Students as respondents also gave a positive response with a questionnaire score of 92.5% showing a very valid quality without revision. The effectiveness of the use of Viktif HAM teaching materials in lectures was calculated by analyzing the results of pre and post tests using N-Gain showing an average of 0.77. So it can be concluded that Viktif HAM human rights teaching materials are effectively used for human rights learning. Keywords: Human Rights Learning, Interactive Video, Teaching Materials